An Optogenetic Arrhythmia Model—Insertion of Several Catecholaminergic Polymorphic Ventricular Tachycardia Mutations Into Caenorhabditis elegans UNC-68 Disturbs Calstabin-Mediated Stabilization of the Ryanodine Receptor Homolog - Engel, Marcial Alexander; Wörmann, Yves René; Kaestner, Hanna; Schüler, Christina (Frontiers in Physiology, 2022)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited disturbance of the heart rhythm (arrhythmia) that is induced by stress, or that occurs during exercise. Most mutations that have been linked to CPVT are found in two genes, i.e. ryanodine receptor 2 (RyR2) and calsequestrin 2 (CASQ2), two proteins fundamentally involved in the regulation of intracellular Ca2+ in cardiac myocytes. We inserted six CPVT-causing mutations via CRISPR-Cas9 into unc-68 and csq-1, the C. elegans homologs of RyR and CASQ, respectively. We characterized those mutations via video-microscopy, electrophysiology and calcium imaging in our previously established optogenetic arrhythmia model. In this study, we additionally enabled high(er) throughput recordings of intact animals by combining optogenetic stimulation with a microfluidic chip system. Whereas only minor/no pump deficiency of the pharynx was observed at baseline, three mutations of UNC-68 (S2378L, P2460S, Q4623R; RyR2-S2246L, -P2328S, -Q4201R) reduced the ability of the organ to follow 4 Hz optogenetic stimulation. One mutation (Q4623R) was accompanied by a strong reduction of maximal pump rate. In addition, S2378L and Q4623R evoked an altered calcium handling during optogenetic stimulation. The 1,4-benzothiazepine S107, which is suggested to stabilize RyR2 channels by enhancing the binding of calstabin2, reversed the reduction of pump ability in a mutation-specific fashion. However, this depends on the presence of FKB-2, a C. elegans calstabin2 homolog, indicating an involvement of calstabin2 in the disease-causing mechanisms of the respective mutations. In conclusion, we showed for three CPVT-like mutations in C. elegans RyR a reduced pump ability upon light stimulation, i.e. an arrhythmia-like phenotype, that can be reversed in two cases by the benzothiazepine S107 and depends on stabilization via FKB-2. The genetically amenable nematode in combination with optogenetics and high(er) throughput recordings is a promising straightforward system for the investigation of RyR mutations and the selection of mutation-specific drugs.